Profit Sharing Dalam Perspektif Hadis - Gus Hendarsih; Repa Hudan Lisalam (Moral : Jurnal kajian Pendidikan Islam, 2025)
Profit sharing or known as profit sharing. This was done at the time of the Prophet Muhammad. In this country, we also often share profits, some with mudhorabah, musyarakah and other systems. To carry out profit sharing, several things are needed in order to get the benefits, firstly justice and honesty, secondly to avoid fraud, thirdly to avoid usury. This research uses a thematic method with regional coverage, the thematic method is in the following way; determine the theme, namely Profit Sharing in a Hadith Perspective, collect data on themes related to the title, provide a final code, analyze the data in the final code then describe the results of the data in the form of an outline. The sources of this data are primary and secondary data. The primary is dancing hadith from several diqital hadith such as Makabah Syamilah, sunnah.com and others. while the secondary is through literature. Profit Sharing is the sharing of profits from profits from companies, agriculture and others. In carrying out Profit Sharing, it requires people who have capital and people who manage it, and both of them must have an agreement, the results of the business they do will be calculated for sharing the results. Profit sharing has several types, namely: mudharabah, musyarakah, muzara'ah and musaqah and Profit sharing also has rules that we must pay attention to, namely; contracts, capital, sharing of results honestly and goods or funds to be managed must be clear.